Cognitive Learning Outcomes of Gas Kinetic Theory Based on InquiryApproach - Pramudya, Clara Tarania; Islami, Nur; Zulhelmi, Zulhelmi; Nor, M. (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of this study is to find the result of students cognitive through the implementation of gas kinetic learning media based on the inquiry approach of XI MIA 3 SMAN 4 Pekanbaru. This research form is pre-experimental with one shot case study method. The data of this study is studentâs cognitive score by the post-test . The analysis conducted on the studentâs cognitive learning outcomes in the form of study absorption, learning effectivity and the percentage of students pass of each tested indicator. The result obtained from this study are, from 36 students, 3 students have a very good study absorption, 23 have a good study absorption, 8 have a good study absorption, 1 has a less good study absorption and 1 fail. The learning effectivity is in a good category with a percentage of 69 ,4%. The conclusion is physics learning with inquiry approach goes well.